The Effect of Marinated Time Spent Laying Hens Meat in Moringa Leaves Extract (Moringa oleifera Lamk.) on Quality of Organoleptic - A. J., Marwansyah; Okarini, I. A.; Miwada, I N.S (Jurnal Peternakan Tropika, 2019)
This research aims is to determine the effect of marinated time spent laying hens meat in moringa leaves extract ( Moringa Oleifera Lamk.) on quality of organoleptic . The implementation  is in Laboratory of Animal Product Technology, Faculty of Animal Husbandry, University of Udayana, Denpasar, this research lasts for 1 week. The research design used is Non-parametric consists of 3 treatments, namely without soaking as control (P 0 ), with 20% soaking of moringa leaves extract for 7 hours (P 1 ), and with soaking 20% moringa leaves extract for 10 hours (P 2 ), each treatment was repeated in 5 times and each replication uses 1 spent laying hens meat without skin, the total is 8 chickens were used with an average thigh and drumsticks weight of 227.4 g. Quality variable organoleptic includes the color of meat, the smell of meat, the texture of meat, the taste of meat, and overall acceptance by panellists (15 Students). The results of the research on raw meat samples and cooked meat samples shows that the color of the flesh, the smell of the flesh, the texture of the flesh, the taste of the flesh, and the overall acceptance of treatment P1 and treatment P2 was not significantly different (P>0.05) decrease the preference value of panelists compared to treatment P0. According to the results the research can be concluded that the soaking in moringa leaf extract  is 20% for 7 hours and 10 hours it has influencetial decrease the quality of organoleptic of meat. Keywords: Spent laying hens meat, quality of organoleptic, moringa leaves extract